Iris and Walter and Cousin Howie - Guest, Elissa Haden (Guest, Elissa Haden. Iris and Walter, 2003)
Walter's favorite cousin is coming to visit, but Iris is disappointed when Howie does not turn out to be so great--or friendly--after all.